PENGARUH KEPEMIMPINAN, PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN BANK RIAU KEPRI CABANG UTAMA PEKANBARU - Sicilia, Gita (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to determine the effect of factors leadership, career development and motivation on job satisfaction of employee of Bank Riau Kepri Main Branch Office Pekanbaru. As the dependent variable is a leadership, career development and motivation, while the independent variable is job satisfaction. The method of analysis used in this study is descriptive statistical analysis method and inferential statistics through Multiple Regression. Methods Research using census method, in which the entire population of as many as 111 employees of Bank Riau Kepri Main Branch Office Pekanbaru, used as a sample as well as research respondents. Before testing the hypothesis, test the validity and reliability of the primary data questionnaire using SPSS version 17.0. Regression equations were then tested with analysis of classical assumption of normality test, Multicollinearity Test, Test Heteroskidastity and Test Autocorrelation. Analysis of the influence of the independent variables with the dependent variable analysis performed with the t test, F test, the coefficient determinant (Adjusted R2) and correlation coefficient (R).Partial results showed leadership factor has no effect on employee job satisfaction but simultantly factors of leadership, career development and motivation has an influence on employee job satisfaction of Riau Kepri Bank Main Branch Office PekanbaruKeywords: Leadership, Career Development, Motivation, Job Satisfaction